Combination of Systems Pharmacology and Experimental Evaluation to Explore the Mechanism of Synergistic Action of Frankincense-Myrrh in the Treatment of Cerebrovascular Diseases - Liao, Yucheng; Wang, Jingwen; Guo, Chao; Bai, Min; Ju, Bowei; Ran, Zheng; Hu, Junping; Yang, Jianhua; Wen, Aidong; Ding, Yi (Frontiers in Pharmacology, 2022)
Frankincense-Myrrh is a classic drug pair that promotes blood circulation, and eliminates blood stasis. The combination of the two drugs has a definite clinical effect on the treatment of cerebrovascular diseases (CBVDs), but its mechanism of action and compatibility have not been elucidated. In this study, the bioactive components, core targets, and possible synergistic mechanisms of Frankincense-Myrrh in the treatment of CBVDs are explored through systems pharmacology combined with in vivo and in vitro experiments. Comparing target genes of components in Frankincense and Myrrh with CBVD-related genes, common genes were identified; 15 core target genes of Frankincense-Myrrh for the treatment of CBVDs were then identified using protein-protein interaction (PPI) analysis. It was also predicted through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis that the molecular mechanism of Frankincense-Myrrh action on CBVDs was mainly related to the regulation of neurotrophic factors and inflammatory responses. Frankincense-Myrrh significantly improved neurological function, decreased infarct volume, alleviated histopathological damage, inhibited microglial expression, and promoted the expression of neurons in middle cerebral artery occlusion (MCAO)-induced rats. The results of this study not only provide important theoretical support and experimental basis for the synergistic effect of Frankincense-Myrrh, but also provide new ideas for the prevention and treatment of cerebral ischemic injuries.